Mengenal Dasar-Dasar Teknik Informatika di SMPN 19 Bulukumba dalam Mempersiapkan Lembaga Era Digital - Ulfa Laela Rambega (Tamilis Synex: Multidimensional Collaboration, 2024)
The aim of preparing the work is to get to know the basics of informatics techniques at SMPN 19 Bulukumba in preparing institutions for the digital era. This research uses qualitative methods to understand the teaching of informatics techniques at SMPN 19 Bulukumba through observation, interviews and documentation. Data were analyzed thematically to identify and interpret key themes related to teaching methods and use of technology. This research provides a comprehensive picture of student preparation for the digital era and can be a reference for other schools. The result of this work is that teaching informatics engineering at SMPN 19 Bulukumba prepares students for the digital era by teaching input devices such as keyboard, mouse, scanner, microphone, and webcam, as well as data processing components such as CPU, RAM, and motherboard. The teacher explains the function and use of output devices such as monitors, printers, speakers and projectors, increasing students' understanding of how to display processed information. The material taught covers the latest theories, providing students with in-depth understanding and relevant practical skills. This teaching improves students' digital skills, the quality of education, and their readiness to face future technological challenges. As a result, students are better prepared to adapt and innovate in the ever-evolving digital era.